Modification and Application of the Polysiloxane with Amino Groups (Journal of Fiber Bioengineering and Informatics, 2008)
A series of the polysiloxanes modified with amino groups are synthesized. FTIR, 1HNMRare used to characterize the polysiloxane structure. Surface properties of the polysiloxane materialswith amino groups are discussed. The results show that the polysiloxanes modified with tertiaryamino groups had good flexibility and repellency to water. With increasing the amino value of thepolysiloxanes, the flexibilities of the fabrics treated with the emulsion were improved. After thesamples were treated with the polysiloxanes, the thermal yellowing had emerged. The whiteness of thefabrics treated with the polysiloxane decreased. The reflectance spectra of the fabrics treated withoutand with the modified polysiloxanes had not significant change.